A case of streptococcus necrotizing fasciitis secondary to acute tonsillitis and review of literatures. Issue 5 (September 2019) - Li, Yongsheng; Liu, Lu; Huang, Zhonghui; Yang, Le; Ye, Yan; Li, Renjie
Necrotizing fasciitis, officially named by Wilson in 1952, was a rare potentially life-threatening necrotizing soft tissue infections disease. The main lesions showed subcutaneous fat and fascia layer in progressive necrosis, generally not involving muscles. It was characterized by acute onset, rapid progress, and dangerous condition, often accompanied by systemic toxin shock, which was a relatively rare clinical acute critical disease with high mortality rate. Necrotizing fasciitis is a rare but clinical critical disease. The overall incidence of necrotizing fasciitis is approximately 0.04 cases per 1000 persons in the United States, the 30-day mortality is 27%, and necrotizing fasciitis–related mortality in Asian region is about 28%. Streptococcus pyogenes (group A streptococcus) are human-specific pathogens that can cause upper respiratory tract infection such as tonsillitis, associated with post-infection diseases such as rheumatic fever, and also can induce severe invasive diseases such as necrotizing fasciitis and streptococcus toxin shock syndrome. This article reports a case of streptococcus necrotizing fasciitis secondary to suppurative tonsillitis, which was seldom reported before and our successful management with delayed debridement. This study was anonymous and was approved by the local Research Ethics Committee. Informed consent was obtained from the patient.